Displacement Behavior of Methane Adsorbed on Coal by CO2 Injection - Zhang, Dengfeng; Li, Songgeng; Cui, Yongjun; Song, Wenli; Lin, Weigang (Industrial & engineering chemistry research, 2011)
The displacement behavior of methane adsorbed on coals by CO2 injection has been experimentally studied. With the assumption of the additive property of the adsorbed-phase volume, a novel data processing method is established to obtain the absolute adsorption amount of methane and CO2 as well as the amount of methane recovery. The results show that the adsorption of CO2 on low-rank Bulianta coal initially saturated with methane is higher than that on high-rank Qinshui coal. For comparison, the adsorption isotherms of pure methane and CO2 on coal without initial methane saturation have been conducted. It is found that, for the coal sample without methane saturation, the CO2 adsorption capacity of high-rank Qinshui coal is superior to that of low-rank Bulianta coal. A conceptual model is proposed to give the explanation. It is indicated that for carbon dioxide sequestration on coal with enhanced coal bed methane recovery (CO2–ECBM), it would be better to inject CO2 after partial desorption of methane by depressurizing in order to improve CO2 storage. The selectivity ratio of CO2 and effects of operation parameters such as pressure and temperature have been discussed. On the basis of the results, a recommended depth of CO2 sequestration in coal seams has been put forward.